WEC program for calculation of systems of accelerating voltage pulses formation on lines with distributed parameters - Gordeev, V.S.; Mikhailov, E.S. (Вопросы атомной науки и техники, 1999)
For some years at VNIIEF there have been developed iron-deprived linear induction accelerators (LIA) [1-3], applying, as basic elements of accelerating system, inductors with water insulation on the base of lines with distributed parameters. When creating such facilities one of the most important tasks is development of systems of forming high-voltage pulses of accelerating voltage with required electric characteristics. On the basis of solving the Maxwell equations system an algorithm of numerical simulation of non-stationary electromagnet processes in axially symmetrical structures consisting of elements with different electric properties (dielectric constant and magnetic permeability, conductivity) is developed. The form of the calculation area is supposed to be rectangular, limits of subareas (elements) separation may be random. There is given a description of applied difference scheme on regular inhomogeneous grid and their realization in the computer program. There is given an example of the program application for calculating electromagnet processes in STRAUS-2 accelerator [4] and their comparison with experimental results.